Rancang Bangun Sistem Manajemen Inventory/Perlengkapan Peralatan Laboratorium Teknik Mesin Universitas Riau - Ervan Kurniawan; Anita Susilawati; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Information technology has been rapidly developed in term of implementations, nowadays. It can be applied to various fields such as the inventory management systems of laboratory. Currently, the laboratory management system in the Mechanical Engineering of University of Riau has used a conventional management system, yet. Therefore, the management of inventory equipments might be not optimize due to still using manual process. The purposes of this research are to design, develop and test of inventory management system based computerize for laboratory equipments in the Mechanical Engineering of University of Riau. The research method was divided into two stages: (1) analyzing of current laboratory conditions by using of visual control/ management and Kanban system and (2) to design, develop and test an information system of inventory management for laboratory’s equipments. A system of application program was created using PHP (Hypertext Preprocessor) as programming language and MySQL as the database. The stages of system design were to develop a database table of subsystem, subsystem models, the dialogues subsystem and display interface system (users interface), and the menus structure. The inventory management based information system that can minimize human error, know exactly the amount of goods and material, be quickly and facilitate a recapitulation and reports, facilitate monitoring and inspection. As a result, the performance of management of inventory/ supplies laboratory equipments in Mechanical Engineering, University of Riau was more optimal, effective and efficient.Keywords: Information System, Laboratory Management, Inventory, MySQL, PHP, Kanban.